Legal Protection for Child Violence Victims in School Environment Based on Law No. 35 of 2014 (Study at SMP Negeri 1 Sunggal) - Nainggolan, Adellina Ahmad Zain; Hadiningrum, Sri (International Journal of Religion Education and Law, 2025)
This study is related to legal protection for victims of child violence in the school environment based on Law no. 35 of 2014 as a case study at SMP Negeri 1 Sunggal. The objectives of this study include explaining the factors causing violence against children at SMP Negeri 1 Sunggal, explaining legal protection against violence against children at SMP Negeri 1 Sunggal, and describing the influence of Law No. 35 of 2014 on efforts to prevent violence against children at SMP Negeri 1 Sunggal. The type of qualitative research used with a descriptive research method that will explain various conditions and situations that arise in society and become objects in the study based on what happened. Samples were taken from 30 students, 1 Principal, 5 BK Teachers and homeroom teachers, and 2 School Employees by purposive sampling. Data will be collected through observation, documentation, and interviews. Then the data will be analyzed based on the Miles and Huberman model (1984), namely activities in qualitative data analysis are carried out interactively through data reduction (data editing), data presentation (data presentation), and verification (drawing conclusions). The results of the study indicate that there are 2 factors causing violence against children in SMP Negeri 1 Sunggal, namely internal and external factors. Legal protection for victims of violence against children in SMP Negeri 1 Sunggal can be achieved through mediation and legal sanctions based on Article 54 of Law Number 35 of 2014. Furthermore, the results of the study also stated that Law Number 35 of 2014 has a good influence because of the firmness of legal sanctions for students who are perpetrators and provides legal protection for students as victims of violence.